Unilateral eyelid ptosis: A case report cured by Gelsemium sempervirens - Nur-; Md. Akther-; Rumana Afroze Rume (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Background: A 60 years-old man presented with an 8-day history of acute onset painless left upper eyelid ptosis covering the pupil entirely. Ptosis can affect unilateral or bilateral. He had no other symptoms; importantly pupils were equal and reactive and eye movements were full. There was no palpable mass or swelling. He had a headache but had no other focal neurological signs or symptoms of fatigue. MRI of brain and Orbits showed no remarkable abnormality detected in brain & orbits.  Objectives: Assessment of the homeopathic symptomatic aspects of Gelsemium sempervirens on eyelid ptosis. Showed homeopathy has a major role in the treatment of ptosis. Materials and Methods. The case management was conducted for 3 weeks and only two follow follow-ups were was taken according to the law of homeopathy.  Result: Administrating Gelsemium sempervirens 30°C of 5/7 pills orally thrice a day for a week; left eyelid ptosis was improved 60%. The ptosis resolved quickly and the patient remains symptom-free 100% at 3 weeks follow-up by next high potency Gelsemium sempervirens 200C with the same pattern.  Conclusion: Acute ptosis may indicate serious pathology. A careful history and examination must be taken. The appropriate management requires recognition of the underlying cause of it. This case presentation highlights the various aspects of ptosis evaluation and management by homeopathy for future study.